On Farm Trial with Rice Fish Cultivation in Nakhon Si Thammarat Southern Thailand - PENGSENG, Puan (Walailak Journal of Science and Technology (WJST), 2013)
The rice-fish culture investigations were conducted at rice farms in Pak Phanang, Nakhon Si Thammarat, Southern Thailand to compare the effect of the rice fish culture model on production performances of rice and fish, income, and net return. All investigations used male Oreochromis niloticus and a native rice variety, Leb Nok Pattani, in 6 plots (5,600 m2 each). Two treatments, sold rice and rice-fish culture were employed with each treatment replicated three times. Juvenile O. niloticus with a mean weight 15 g were stocked to give 1.25 individuals per m2 30 days after sowing the rice. Rice seeds, 15 kg rai-1 (rai = 1,600 m2), were planted and commercial organic fertilizer, 100 kg rai-1, was applied. Commercial feed was used as a supplementary feed, equivalent to 2 % fish body weight, once daily. The fish and rice were harvested after 122 days and 185 days, respectively. The results indicated that the rice-fish culture gave an average gross yield of 216 ± 37 and 1,122 ± 77 kg rai-1 for fish and rice, respectively and differed (p < 0.05) from the rice monoculture treatment with an average rice yield of 686 ± 96 kg rai-1. In addition, the rice monoculture gave an average total income and net return of 5,490 and 1,719 baht rai-1 respectively while for the rice-fish culture treatment values of 17,538 and 7,338 baht rai-1 respectively were found indicating the treatments are significantly different (p < 0.05). Therefore, adoption of this system will not only increase rice production but also generate additional animal (fish) protein. Moreover, farmers who grow fish and rice together in the same area can also increase their income.